Fibroblast heterogeneity and FN1-mediated signaling in endometriosis revealed by single-cell and spatial transcriptomics - Shao, Wenwen; Ju, Hongmei; Xiahou, Zhikai; Fang, Sheng; Yan, Rugen; Li, Chunyan; Xu, Yuan; Cai, Pingping (Frontiers in Immunology, 2025)
BackgroundEndometriosis (EM) is a chronic gynecological disorder that affects 5% to 10% of women of childbearing age, often causing pelvic pain and infertility. Fibrosis is a hallmark of EM progression, yet its underlying molecular drivers remain poorly understood. Emerging progress in single-cell and spatial transcriptomic technologies offer new opportunities to unravel the cellular heterogeneity and intercellular interactions driving fibrotic and immune remodeling in EM lesions.MethodsWe performed an integrative multi-omics analysis combining single-cell RNA sequencing (scRNA-seq) and spatial transcriptomics to dissect fibroblast heterogeneity and cell–cell communication networks in EM. ScRNA-seq data from 15 EM patients (GSE213216) were processed to identify transcriptionally distinct fibroblast subpopulations. Functional enrichment (GO, GSEA), stemness estimation (CytoTRACE), and trajectory inference were applied to reveal lineage plasticity. CellChat was used to infer intercellular signaling networks, and spatial transcriptomic data from two ectopic lesions (GSM6690475, GSM6690476) were analyzed to validate the spatial distribution of key ligand–receptor interactions.ResultsWe identified 35 cell clusters across EM lesions, with Fibroblast and T/NK cells as dominant populations. Fibroblast were divided into five subtypes, which were associated with extracellular matrix remodeling, immune interactions, and metabolic regulation. Notably, the C2 CXCR4+ Fibroblast subpopulation exhibited high proliferative capacity and stemness characteristics, and mediated signaling pathways involved in immune and fibrotic responses through FN1. Spatial transcriptomic analysis confirmed the local enrichment of these Fibroblast in ectopic lesions, where they were associated with regions of active signaling.ConclusionThis study revealed the transcriptional and spatial heterogeneity of Fibroblast in EM syndrome, and identified the C2 CXCR4+ Fibroblast subpopulation as a may represent key driver of fibrosis and immune regulation. Our integrated omics approach provided new mechanistic insights into the pathogenesis of EM and pointed out new targets for therapeutic intervention.